Design and Implementation of an Intranet Security and Access Control System in Ubi-Com - Lee, Malrey; Cho, Nam Deok; Lee, Keun Kwang; Ko, Kyoung Sook (COMPUTING AND INFORMATICS, 2012)
Currently, most enterprise intranet systems process user information for security and access authentication purposes. However, this information is often captured by unauthorized users who may edit, modify, delete or otherwise corrupt this data. In addition, corruption can result from inaccurate communication protocols in the web browser. Therefore, a method is needed to prevent unauthorized or erroneous access and modification of data through the intranet. This paper proposes an efficient security procedure that incorporates a new model that allows flexible web security access control in securing information over the intranet in UC. The proposed web security access control system improves the intranet data and access security by using encryption and decryption techniques. It further improves the security access control by providing authentication corresponding to different security page levels relevant to public ownership and information sensitivity between different enterprise departments. This approach reduces processing time and prevents information leakage and corruption caused by mistakes that occur as a result of communication protocol errors between client PC’s or mail security methods.